“Entre a véspera e o porvir”: a tradição das Musas na poesia de Geraldo Carneiro - ABREU, Fernanda Castro de Souza (2023)
Through the reading of Poemas Reunidos (2010), by Geraldo Carneiro, it is possible to notice a variety of forms that the Muse is presented, referring directly or indirectly to the inspiring gods of previous traditions. Having this in mind, this thesis aims to analyze the Muses’ shapes and motives in Geraldo Carneiro’s poetry, observing the connections with other authors through intertextual dialogues and highlighting the particularities of the theme use. In this regard, at first, we discuss the iconic uses of the Muses’ image, from archaic tradition to Brazilian Marginal Poetry of the 1970s, and in works of Dante, Petrarca, Camões, Álvares de Azevedo, Fernando Pessoa, Manuel Bandeira and Antonio Carlos Secchin, in order to trace briefly a variation mosaic that the theme has received through Western Poetry history. The characteristics we mark are significant to the topos comprehension, as the meaning layers created over time help to form the Muses and inspiration idea, leading to Geraldo Carneiro’s work. Secondly, this research discusses the “ecstasy” concept, traditionally associated with inspiration. The topic will be addressed with the reading of Michel Collot’s text “O sujeito lírico fora de si”, going to another perspective on the movement of getting out of self, leading to the question of the second chapter: “how can the outward movement bring a connection to another self?”. The hypothesis is that Carneiro’s lyric subject uses the different shapes of the Muses as a driving force of the topos work. In chapter three, we analyze the different profiles they get in Geraldo Carneiro’s poetry, such as gods, women-muses and poetry itself. Lastly, we check Carneiro’s own poetic traits, demonstrating their paths and variations on the theme use over his 40-year poetic journey. It is possible to see, through research, that thinking about the Muses involves thinking about poetry itself: its production and values. The theoretical framework is composed, mainly, of Plato’s dialogues Phaedrus and Ion, Hesiod’s Teogony – as well as Jaa Torrano’s introductory study in the 2005 edition, “O mundo como função de Musas” –, A herança de Apolo by Geraldo Cavalcante, European Literature and the Latin Middle Ages by Ernst Robert Curtius, The Mirror and the Lamp by Meyer Howard Abrams, The Other Voice by Octavio Paz and the thesis “A máquina do mundo requebrada: poética, metapoesia e intertextualidade em Geraldo Carneiro” by Leonardo Vivaldo.